Design and validation of a six-antenna WPT system with tracking capabilites for biomedical devices - Dinis, Hugo Daniel Costa (2019)
Reliable powering of implantable medical devices is a key requirement for the development of ever-so-small sensors and actuators. The difficulty of this task becomes even greater when the device is meant to travel inside the human body. This paper presents a 2 GHz RF WPT system capable of tracking an implantable device and maximizing the amount of power transferred to it along its path. Measurements and simulations were performed to validate the system, and the use of tracking increased the amount of available power for the implant along its path in all the studied points comparatively to the scenario where no tracking was used. This technology presents itself as a promising stepping stone towards battery-less implantable medical devices.